2022
DOI: 10.1371/journal.pntd.0009889
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiles of Schistosoma japonicum larval stages: Implications for parasite biology and host invasion

Abstract: Schistosoma japonicum is prevalent in Asia with a wide mammalian host range, which leads to highly harmful zoonotic parasitic diseases. Most previous transcriptomic studies have been performed on this parasite, but mainly focus on stages inside the mammalian host. Moreover, few larval transcriptomic data are available in public databases. Here we mapped the detailed transcriptome profiles of four S. japonicum larval stages including eggs, miracidia, sporocysts and cercariae, providing a comprehensive developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…S8C), and it encodes a metallopeptidase named Neprilysin4 (Additional file 2 : Table S9; Additional file 1 : Fig. S7) that is thought to aid the parasite in escaping the immune attack of O. hupensis after invasion by miracidia [ 53 ]. Nep4 was highly expressed in the miracidium, a critical offstage in the invasion of intermediate hosts (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S8C), and it encodes a metallopeptidase named Neprilysin4 (Additional file 2 : Table S9; Additional file 1 : Fig. S7) that is thought to aid the parasite in escaping the immune attack of O. hupensis after invasion by miracidia [ 53 ]. Nep4 was highly expressed in the miracidium, a critical offstage in the invasion of intermediate hosts (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, snails from the Yunnan and Sichuan provinces grouped in separate clades on the phylogenetic tree [ 97 ], a result that may be related to the difference in Rab6 haplotypes between the two populations. Besides, Nep4 encodes Neprilysin4, a protein that may be involved in the inactivation of the snail host’s immunocytes [ 53 ]. RNA-seq data showed that Nep4 was highly expressed at the miracidia stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schistosomiasis is a zoonosis caused by Schistosoma parasites that is widely prevalent in tropical and subtropical areas and has drawn limited research attention [ 1 , 2 ]. There are multiple types of schistosomes, mainly including Schistosoma aegypti , S. mansoni , and S. japonicum [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ]; Clonorchis sinensis [ 21 , 22 , 23 ]; Schistosoma spp. [ 24 , 25 , 26 ]; and Fasciola hepatica [ 27 , 28 , 29 ]. To obtain transcriptomic insights into the differential expression of the stage-specific gene in N. fowleri , this study used RNA-Seq to analyze the transcriptome of N. fowleri cysts transferred to encystment buffer for 3 days compared with an N. fowleri trophozoite control group.…”
Section: Introductionmentioning
confidence: 99%